Frequency of Prediabetes in Patients With High BMI Presenting to a Tertiary Care Hospital - Shehzad, .; Kalimullah, .; Hanan, Abdul; Yasir, .; Fawadullah, . (Biological and Clinical Sciences Research Journal, 2025)
Prediabetes is characterized by elevated blood sugar levels but not yet diabetes. Preventive interventions are crucial to prevent the progression to full-blown diabetes. Objective: This study aimed to determine the Frequency of prediabetes in patients with high BMI presenting to a tertiary care hospital. Method: The current cross-sectional study was conducted at the Department of Medicine, Qazi Hussain Medical Complex, Nowshera, over 6 months (July to December 2024) after taking permission from the ethical board of the institute. A total of 126 individuals with high BMI (body mass index 25 ≥ kg/m2) of both genders and different age groups (18-85 years) were included. Demographic data, including BMI, gender, age, education, employment, residence, and socioeconomic position, were collected. A history of hypertension and smoking was also reported. Participants with a high BMI were tested for pre-diabetes using Fasting Plasma Glucose (FPG) or Hemoglobin A1c (HbA1c) evaluations. Data was analyzed through SPSS version 25. The post-stratification chi-square or Fisher’s exact test was applied to determine the significance. Results: A total of 126 individuals were screened in this study, out of which 20(15.8%) were found to be pre diabetes. Of the prediabetes individuals, 13 (65%) were males and 7(45%) were females. In this study, 75% of individuals had a family history of diabetes, one of the prediabetes risk factors. Most research participants (50%) come from lower-income families and live in rural regions (75%). A history of hypertension was observed in 85% of the individuals, and smoking in 70% of the participants. The majority (90%) were overweight, while 10% were obese. The Chi-Square test results showed values of 0.03, showing a strong association between prediabetes and body mass index (p-value <0.05). Conclusion: The present study concluded that the Frequency of prediabetes was 15.8% in patients with high BMI 15.8%. A significant association exists between prediabetes and BMI (Chi square = 0.31, p-value < 0.05).